Applications of beneficial plant growth promoting rhizobacteria and mycorrhizae in rhizosphere and plant growth: A review - Khan, Ashiq; Ding, Zitong; Ishaq, Muhammad; Khan, Israr; Ahmed, Anum Ali; Khan, Abdul Qadir; Guo, Xusheng (International Journal of Agricultural and Biological Engineering, 2020)
Because of climate change and the highly growing world population, it becomes a huge challenge to feed the whole population. To overcome this challenge and increase the crop yield, a large number of fertilizers are applied but these have many side effects. Instead of these, scientists have discovered beneficial rhizobacteria, which are environmentally friendly and may increase crop yield and plant growth. The microbial population of the rhizosphere shows a pivotal role in plant development by inducing its physiology. Plant depends upon the valuable interactions among the roots and microbes for the growth, nutrients availability, growth promotion, disease suppression and other important roles for plants. Recently numerous secrets of microbes in the rhizosphere have been revealed due to huge development in molecular and microscopic technologies. This review illustrated and discussed the current knowledge on the development, maintenance, interactions of rhizobacterial populations and various proposed mechanisms normally used by PGPR in the rhizosphere that encouraging the plant growth and alleviating the stress conditions. In addition, this research reviewed the role of single and combination of PGPR, mycorrhizal fungi in plant development and modulation of the stress as well as factors affecting the microbiome in the rhizosphere. Keywords: rhizosphere, plant growth promoting rhizobacteria, mycorrhizae, nitrogen fixing bacteria, phosphate solubilizing bacteria DOI: 10.25165/j.ijabe.20201305.5762 Citation: Khan A, Ding Z T, Ishaq M, Khan I, Ahmed A A, Khan A Q, et al. Applications of beneficial plant growth promoting rhizobacteria and mycorrhizae in rhizosphere and plant growth: A review. Int J Agric & Biol Eng, 2020; 13(5):199–208.